The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1002/path.1877
|View full text |Cite
|
Sign up to set email alerts
|

The function of immunoglobulin A in immunity

Abstract: The vast surfaces of the gastrointestinal, respiratory, and genitourinary tracts represent major sites of potential attack by invading micro-organisms. Immunoglobulin A (IgA), as the principal antibody class in the secretions that bathe these mucosal surfaces, acts as an important first line of defence. IgA, also an important serum immunoglobulin, mediates a variety of protective functions through interaction with specific receptors and immune mediators. The importance of such protection is underlined by the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
460
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(493 citation statements)
references
References 118 publications
7
460
1
6
Order By: Relevance
“…In addition, immune responses in the aforementioned mammalian mucosal surfaces present also commonalities with those observed here in the fish skin. Thus, it has also been shown that microbial infections in these mammalian mucosal surfaces generally induce a local mucosal response governed by a mucosal Ig (sIgA) and that, in some cases, the systemic response is dominated by IgG/IgM (31,32). Moreover, similar to the accumulations of IgT + B cells shown here in the skin epidermis of infected fish, significant accumulations of B cells have also been described upon infection in the MALT of nose (33), gut (16,34), lung (35), and uterus (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immune responses in the aforementioned mammalian mucosal surfaces present also commonalities with those observed here in the fish skin. Thus, it has also been shown that microbial infections in these mammalian mucosal surfaces generally induce a local mucosal response governed by a mucosal Ig (sIgA) and that, in some cases, the systemic response is dominated by IgG/IgM (31,32). Moreover, similar to the accumulations of IgT + B cells shown here in the skin epidermis of infected fish, significant accumulations of B cells have also been described upon infection in the MALT of nose (33), gut (16,34), lung (35), and uterus (36).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the upper domains of the Fc region (the C H 1 domains), the domains are arranged in pairs, stabilized by numerous non-covalent trans interactions. 7 In humans, IgAs are divided into closely related subclasses, IgA1 and IgA2, which differ by the absence of a 13-amino acid sequence in the hinge region of the IgA2 molecule. 1 The lack of this region in IgA2 allows it to be resistant to the action of bacterial proteases (i.e., those from Streptococcus mutants, Neisseria meningitidis and Haemophilus influenzae) that cleave IgA1 in the hinge region and may underlie the predominance of IgA2 in mucosal secretions.…”
Section: Structure Of Igamentioning
confidence: 99%
“…1 The lack of this region in IgA2 allows it to be resistant to the action of bacterial proteases (i.e., those from Streptococcus mutants, Neisseria meningitidis and Haemophilus influenzae) that cleave IgA1 in the hinge region and may underlie the predominance of IgA2 in mucosal secretions. 7 IgA SYNTHESIS The forms of IgA in serum and mucosal secretions, the two main compartments in which these antibodies are found, differ. In serum, IgA exists mainly in its monomeric form (about 85-90%).…”
Section: Structure Of Igamentioning
confidence: 99%
See 1 more Smart Citation
“…M ore IgA is produced per day in the human body than all of the other antibody isotypes combined (1). Humans express two IgA isotypes, IgA1 and IgA2, and each isotype is expressed in several oligomeric states including, monomeric (mIgA), dimeric (dIgA), and secretory (S-IgA) (1).…”
mentioning
confidence: 99%